Spinal epidural abscess in a juvenile dog - Schmiedt, C. W.; Thomas, W. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
A six-month-old, intact female, Miniature Pinscher was admitted with signs of progressive neurological deficits in the hind legs, an elevated rectal temperature, and spinal pain of 48 hours duration. A myelogram was performed which demonstrated a dorsal, left sided compressive lesion extending from T11-T13. A leftsided hemilaminectomy was performed from T11-T13. A friable, poorly organized, pale tan and red mass was identified within the epidural space. Cytopathological and histopathological analyses of the mass demonstrated marked, subacute, suppurative cellulitis. A culture of the purulent material revealed beta haemolytic Streptococcus sp.
Keywords: Spinal epidural abscess; juvenile; dog